Establishment of a High Throughput Screening System for GABAA1 Modulators in Living Cells - Zhang, Yi; Shi, Tong; Chen, Xuejun; Zhang, Ruihua; Shi, Jingjing; Jin, Qian; Xu, Jianfu; Wang, Chen; Li, Liqin (Combinatorial Chemistry & High Throughput Screening, 2023)
Background: The incidence of sleep disorders is more than 27% in the worldwide, and the development of novel sleep drugs that target GABAA receptors is of great interest. Traditional drug screening methods restrict the discovery of lead compounds, the high-throughput screening system is a powerful means for the lead compounds discovery of sleep drug. Methods: The GABAA1-CHO cell line stably expressing α1β2γ2L was constituted by cotransfection of α1, β2 and γ2L subunits into CHO-T-Rex cells. The high-throughput screening method of membrane potential targeting GABAAR was established and optimized. The optimized method was used to screen the compound library, and the compounds with high activity were obtained. The active compounds were confirmed in vitro by electrophysiological detection technique, and the sleep effects of compounds in vivo were detected by pentobarbital sodium sleep model in mice. Results: A stable cell line expressing human GABAA1 receptor in CHO-T-Rex cells was generated and used to establish a functional high-throughput screening assay based on the measurement of membrane potential changes in living cells by fluorometric imaging plate reader (FLIPR). The assay was further used to detect the dose-effect relationships of tool compounds, the EC50 values of agonist GABA (137.42 ± 26.31 nM), positive allosteric modulator diazepam (3.22 ± 0.73 μM), and antagonist gabazine (0.16 ± 0.04 μM), blocking agents bicuculine (0.47 ± 0.06 μM) and PTX (6.39 ± 1.17 μM). In the meanwhile, the compounds were screened from a compound library (10000) by the membrane potential dye assay. Selected 4 active compounds were further identified for their EC50 values in vitro by electrophysiological method, the EC50 values of 4 compounds were further determined as 1.37 ± 0.43 μM, 0.69 ± 0.17 μM, 0.77 ± 0.16 μM, and 1.62 ± 0.29 μM. Furthermore, the pentobarbital sleep rate and the sleep time of mice pretreated with 4 active compounds by oral administration were significantly increased compared with mice pretreated with a negative control in vivo experiment. Conclusion: We successfully generated a stable CHO cell line expressing human GABAA1 by induced expression strategy which decreased cytotoxicity. Then, developed an efficient membrane potential detection method for high-throughput screening, the assay based on the stable cell line could distinguish different types of GABAA1 modulators, which would be an effective in vitro system to screen the GABAAR-targeted compounds. Compared with the patch clamp electrophysiological detection method, the membrane potential detection method has higher detection flux for compounds and higher detection sensitivity for active compounds.
Keywords: screen